2017
DOI: 10.1080/17512433.2017.1362979
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP2D6 phenotype in the Yoruba Nigerian population

Abstract: Background: There is a lack of information on CYP2D6, a major metabolizing enzyme, in Africa ethnic nationalities. The objective was to determine CYP2D6 phenotype in Yoruba Nigerians using dextromethorphan (DEX). Method: A total of 89 healthy volunteers received 30 mg of DEX orally followed by blood and urine sample collection at 3-hour and over 8 hours post-dose, respectively. DEX and dextrorphan (DOR) concentrations were determined using High Performance Liquid Chromatography (HPLC). The metabolic ratio (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Prior studies reported a good correlation between serum and urine metabolic ratios for dextromethorphan and its primary metabolite, suggesting either serum or urine metabolic ratios can be used for phenotype assessment of PMs and NMs. 24,39 However, the benefit of the serum metabolic ratio in discriminating IMs from NMs is not yet proven. 24 In our study, both plasma and urinary metabolite exposure ratios could discriminate CYP2D6*17*17 and CYP2D6*29*29 genotypes from CYP2D6*1/*2 diplotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies reported a good correlation between serum and urine metabolic ratios for dextromethorphan and its primary metabolite, suggesting either serum or urine metabolic ratios can be used for phenotype assessment of PMs and NMs. 24,39 However, the benefit of the serum metabolic ratio in discriminating IMs from NMs is not yet proven. 24 In our study, both plasma and urinary metabolite exposure ratios could discriminate CYP2D6*17*17 and CYP2D6*29*29 genotypes from CYP2D6*1/*2 diplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite ratios of desipramine also showed a similar trend. Prior studies reported a good correlation between serum and urine metabolic ratios for dextromethorphan and its primary metabolite, suggesting either serum or urine metabolic ratios can be used for phenotype assessment of PMs and NMs 24,39 . However, the benefit of the serum metabolic ratio in discriminating IMs from NMs is not yet proven 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In spite of general consensus, by various African researchers, about the need to carry out more robust pharmacogenomics studies, there remains constraints of funding, technology and human capacity [18,19]. In this regard, the emerging role for pharmacogenomics in HIV research in Africa, could remain a pipedream, unless there is training and funding, together with technology and human capacity building, for such work.…”
mentioning
confidence: 99%